Community Perceptions of East Aceh District in Sustainable Management of Mangrove Ecosystem - Rahmawati Rahmawati; Muhammad Arif; Rosi Rahayu; Akbardiansyah Akbardiansyah (Jurnal Kelautan dan Perikanan Indonesia, 2023)
Mangrove ecosystems have of benefits variety and enhance the economic potential of coastal communities. Changes in land use and utilization of mangrove areas are excessive in the coastal area due to the destructive activities of the community, so mangrove ecosystem management needs to be done so that the ecosystem can be preserved. The existence of the community around this ecosystem has a role that is no less important for the sustainability of mangroves. This research aims to identify and analyze the community’s perception regarding the utilization of the mangrove ecosystem. The study was conducted on the perception of society with perception analysis using the Likert scale. The results of the analysis showed that 77 percent of total respondents strongly agree regarding the functions of the mangrove ecosystem area as filter seawater, breaking waves and feeding ground. Mangrove ecosystems provide benefits to society in the form of the main source of income as much as 78 percent of total respondents and 63 percent strongly agreed with the State of the mangrove ecosystems have been degraded. Next 40 percent strongly agree conversion of land into Palm and 27 percent conversion into ponds aquaculture. Community attitudes support plan sustainable mangrove ecosystem management shown by 75 percent and amounted to 65 percent support the efforts of community training and support community involvement 70 percent of communities in the management of sustainability.Keywords: Activities of Community, Mangrove, Perception